2020
DOI: 10.3390/su12166522
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Dimensions and Adolescent Peer Aggression: A Gendered Analysis

Abstract: The present study had two main goals. The first was to analyze the differences between parenting dimensions—strictness/imposition and involvement/acceptance—in adolescents’ engagement in peer aggression as aggressors, victims, aggressive victims, and non-involved. The second goal was to examine differences between parenting dimensions and peer-aggression roles by gender of both parents and adolescents. Participants were 779 adolescents (49.16% boys and 50.84% girls), aged between 12 and 16 years old (M = 14.21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…However, the perception of family conflict contributes to the fact that adolescents are victims of victimization, since they tend to perform submissive behaviours and present themselves to their peers as vulnerable and easy targets for abuse [46]. Victims of PV define their parents as cold, indifferent, hostile, in some cases overprotective or permissive and feel rejected and little supported by them [47,48]. In addition, communication problems and family expressiveness have been observed in victims, increasing the psychological discomfort of adolescents, who find it more difficult to deal effectively with aggression [12,32].…”
Section: Child-to-parent Violence Peer Victimization and Cybervictimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the perception of family conflict contributes to the fact that adolescents are victims of victimization, since they tend to perform submissive behaviours and present themselves to their peers as vulnerable and easy targets for abuse [46]. Victims of PV define their parents as cold, indifferent, hostile, in some cases overprotective or permissive and feel rejected and little supported by them [47,48]. In addition, communication problems and family expressiveness have been observed in victims, increasing the psychological discomfort of adolescents, who find it more difficult to deal effectively with aggression [12,32].…”
Section: Child-to-parent Violence Peer Victimization and Cybervictimizationmentioning
confidence: 99%
“…This process is bi-directional; greater PV also implies greater psychological distress, which in turn makes adolescents have worse communication with their parents [20]. However, positive parent-adolescent relations, including positive communication and disclosure between parents and children implies better psychosocial adjustment and a lower level of victimization among peers [33,47].…”
Section: Child-to-parent Violence Peer Victimization and Cybervictimizationmentioning
confidence: 99%
“…que constituyen factores predisponentes, precipitantes o mantenedores de la agresividad juvenil. Sin embargo, la mayoría de estos estudios se han realizado con población normal escolarizada (Batool y Bond, 2015;Montero-Montero et al, 2020;Lakhdir et al, 2020;Ojedokun et al, 2013;Sharma, 2016). Asimismo, existe una amplia literatura sobre la agresividad juvenil en población normal (Estévez et al, 2018;Robles-Haydar et al, 2021;Sánchez, 2018), pero no se encuentran estudios que analicen la agresividad de padres y madres de jóvenes delincuentes.…”
Section: Introductionunclassified
“…More specifically, peer aggression is considered to be a public health issue [ 4 ] that affects the well-being of children and adolescents [ 5 ], and even the development of their adult life, making it a complex problem. Previous research has identified various risk factors [ 6 , 7 ], and personal and social adjustment problems [ 8 , 9 ], associated with peer aggression and peer victimization.…”
Section: Introductionmentioning
confidence: 99%